The Linguistic Register of 3 Maccabees and its Sociocultural Implications - Comins, Ryan (Journal of septuagint and cognate studies, 2024)
The Greek of 3 Maccabees contains numerous rare lexical items and notable syntactic constructions which have scarcely been analysed or contextualised within the extant corpus of Postclassical Greek. In this article, several of these lexical and syntactic features are situated within their contemporary sociolinguistic context and analysed from the perspective of register. The implications of this linguistic evidence for our understanding of the social background of 3 Maccabees and its Jewish Greek cultural identity are then examined.